Investigation of Pollutants Derived from Municipal Solid Waste Combustion in a Small Incinerator - Unchaisri, Thanet; Chayawattana, Tanong; Poosri, Jaruwan; Dechsatian, Apinya; Chaivatamaset, Pawin (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2025)
The experimental study of pollutants derived from municipal solid waste combustion in a small incinerator of waste aims to determine the appropriate waste quantity for combustion in the incinerator, and to investigate the release of pollutants during waste combustion. Municipal solid waste was used in the experiments, and there were three feeding levels: 4, 3, and 2.9 kg/batch. The wood and the fresh waste were applied for co-firing with the dry municipal solid waste. The mass fractions of wood and fresh waste were at 26.7 wt% and 10.3 wt%, respectively. The combustion chamber's internal temperature, the temperature of exhaust gases, and the pollutants, such as carbon monoxide (CO), nitrogen oxides (NOx), and sulfur dioxide (SO2), were all factors that were examined. The incinerator was made of steel that was a thickness of 3 mm, a waste feed opening size of 55 x 55 x 55 cm (width x length x depth), and an internal diameter of 25 cm with a height of 90 cm. The study results revealed that the suitable feeding rate was at 2.9 kg/batch, which contained a mixture of fresh waste (10.3 wt%), with the combustion chamber temperature varied in range of 400 - 500 oC and the unburned carbon content of 12.3 wt%. The pollutants emitted from waste incineration were at 6,843 ppm of CO, 302 ppm of NOx, and 574 ppm of SO2, which exceeded the pollutant standard limits, especially SO2, which resulted from the main component of municipal solid waste being plastic in the waste mixture at a ratio of 52.1 wt%.